Functional capacities and sport-specific skills of 14- to 15-year-old male basketball players: Size and maturity effects - Coelho e Silva, M. J.; Figueiredo, A. J.; Moreira Carvalho, H.; Malina, R. M. (European Journal of Sport Science, 2008)
The aim of the study was to estimate the influence of body size and pubertal status on variation in functional capacities and sport-specific skills of 59 youth basketball players aged 14.0-15.9 years. Height and mass were measured and stage of pubic hair was assessed at clinical examination. Six tests of functional capacity were evaluated: squat jump, countermovement jump, 60-s sit-ups, 2-kg standing medicine ball throw, hand grip strength, and 20-m multi-stage shuttle run. Four basketball skills were tested (shooting, passing, dribbling, and defensive movements). Comparisons between basketball players of different sexual maturity status were performed using analysis of covariance (controlling for chronological age). Functional capacities and basketball skills appeared to be largely independent of pubertal status especially after controlling for variation in body size. Results of multiple linear regressions indicated chronological age as a significant predictor for four items, while maturity status was a significant predictor for only one item. The influence of body mass was negative for two functional indicators (jumping, multi-stage shuttle run) and two basketball skills (dribbling, defensive movements), but positive for two functional tests of upper body strength (hand grip, ball throw). Height was positively correlated with two specific skills (passing, defensive movements), while a combination of tallness and heaviness was associated with a disadvantage on three functional capacities and two sport-specific skills.